Morphological changes in vertebral synchondroses in an experimental model of hypothyroidism - Talibnazarova Dildora Dilshatovna; T.F.N. Mirzaev Dilshodbek Ahmedovich (Peerian Journals Publishing, 2025)
This study investigates the morphological alterations of spinal synchondrosis under experimental hypothyreosis. The research focuses on structural, histological, and biochemical changes in the vertebral synchondroses, aiming to understand how thyroid hormone deficiency affects skeletal tissue formation and ossification processes. The results reveal significant degenerative and dystrophic modifications in the cartilaginous components, delayed ossification, and vascular changes that collectively impair spinal stability and growth. These findings contribute to the broader understanding of endocrine influences on the vertebral system and may support new diagnostic and therapeutic approaches in endocrinopathies affecting skeletal tissues.
Keywords: Spinal synchondrosis; hypothyreosis; morphology